2005
DOI: 10.2337/diacare.28.4.810
|View full text |Cite
|
Sign up to set email alerts
|

The Relation Between Hyperglycemia and Outcomes in 2,471 Patients Admitted to the Hospital With Community-Acquired Pneumonia

Abstract: OBJECTIVE— To examine whether hyperglycemia at the time of presentation was associated with outcomes in patients admitted to non–intensive care settings with community-acquired pneumonia (CAP). RESEARCH DESIGN AND METHODS— Prospective cohort study of consecutive patients admitted to six hospitals between 15 November 2000 and 14 November 2002. RESULTS— Of the 2,471 patients in this study (median age 75 years), 279 (11%) had serum glucose at presentation >11 mmol/l: 178 of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
274
3
15

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 400 publications
(305 citation statements)
references
References 35 publications
13
274
3
15
Order By: Relevance
“…Our estimated 1.8-fold overall increase in mortality among heart failure patients was slightly lower than the odds-ratio-based estimate of 2.4-fold mortality increase associated with congestive heart failure, calculated in meta-analysis of pneumonia prognosis by Fine et al 26 , based on six pneumonia outcome studies (conducted between 1966 and 1995) with data on heart failure. Our crude MRR was similar to that published in a recent Canadian cohort study of pneumonia patients [crude relative risk for in-hospital mortality with heart failure=1.65 (95% CI 1.20-2.29); adjusted estimate not given] 22 . However, our findings showed that much of the mortality increase associated with heart failure disappeared after controlling for age and comorbidity.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Our estimated 1.8-fold overall increase in mortality among heart failure patients was slightly lower than the odds-ratio-based estimate of 2.4-fold mortality increase associated with congestive heart failure, calculated in meta-analysis of pneumonia prognosis by Fine et al 26 , based on six pneumonia outcome studies (conducted between 1966 and 1995) with data on heart failure. Our crude MRR was similar to that published in a recent Canadian cohort study of pneumonia patients [crude relative risk for in-hospital mortality with heart failure=1.65 (95% CI 1.20-2.29); adjusted estimate not given] 22 . However, our findings showed that much of the mortality increase associated with heart failure disappeared after controlling for age and comorbidity.…”
Section: Discussionsupporting
confidence: 84%
“…In our study, the overall 30-day mortality from pneumonia was higher than that reported in previous selected patient cohorts or hospitals 11,22,25 , most likely because we had access to comprehensive population-wide health information, covering nursing-home residents and all types of hospitals 13 . Our estimated 1.8-fold overall increase in mortality among heart failure patients was slightly lower than the odds-ratio-based estimate of 2.4-fold mortality increase associated with congestive heart failure, calculated in meta-analysis of pneumonia prognosis by Fine et al 26 , based on six pneumonia outcome studies (conducted between 1966 and 1995) with data on heart failure.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…Patients with cardiovascular, infectious, and neurological problems are particularly sensitive to changes in glycemia. [33][34][35][36][37] In critically ill patients, mortality is positively correlated with increasing glucose levels [ 5 mmolÁL -1 , 38 and in patients undergoing cardiovascular procedures, hyperglycemia was associated with increased mortality and organ dysfunction. 39 Patients with fasting glucose levels [ 7 mmolÁL -1 or random blood glucose levels [ 11.1 mmolÁL -1 on general surgical wards had an 18-fold increase in in-hospital mortality, a longer stay, and a greater risk of infection.…”
Section: Glucose Metabolismmentioning
confidence: 99%
“…4 Hyperglycemia is a strong predictor of adverse clinical outcome in a range of diseases such as acute stroke, congestive heart failure, communityacquired pneumonia, and acute myocardial infarction. [5][6][7][8] Hyperglycemia is also a risk factor for surgical infection in patients undergoing cardiac surgery. 9,10 A landmark prospective randomized controlled clinical trial by van den Berghe et al 11 demonstrated that tight glucose control (target blood glucose level 80-110 mg/dL) with intravenous insulin in critically ill surgical patients led to dramatic reductions in acute renal failure, critical illness polyneuropathy, hospital mortality, and bloodstream infection.…”
mentioning
confidence: 99%